PENERAPAN METODE PROSES PRODUKSI DALAM PERDAGANGAN INTERNASIONAL UNTUK PERLINDUNGAN LINGKUNGAN DAN KESEHATAN - Sri Wartini; Risky Edy Nawawi (Jurnal Media Hukum, 2015)
Processes and Production Methods (PPMs) are the subject of one of the most complicated controversies in the debate over international trade and protection of the environment and human health.  The issue of PPMs actually is not prohibited under the WTO system. There are some cases which may become evident to prove that PPMs is permisible in WTO system. However, PPMs for some rasons can be used as a tool of disguise protectionism by the developed countries. Unfortunately, a developing country finds difficulty to challenge it.  The article emphasizes in   a weighty examination of the two  issues , namely : (i)What are the justifications of process and production method (PPMs) to implement  in international trade? (ii) What are the legal implication of PPMs in international trade to the protection of the environment and the human health ? The research method is qualitative and the approach of the research is normative. The research finds that the implementation of PPMs to some extend are justifiable in international trade to the extent that comply with the provisions of the General Agreement on Tariffs and Trade (GATT),  the Agreement on Sanitary and Phytosanitary Measures (SPS), and  the Agreement on Technical Barriers to Trade (TBT) Agreement.